Duality, Matroids, Qubits, Twistors, and Surreal Numbers - Nieto, J. A. (Frontiers in Physics, 2018)
We show that via the Grassmann-Plücker relations, the various apparent unrelated concepts, such as duality, matroids, qubits, twistors, and surreal numbers are, in fact, deeply connected. Moreover, we conjecture the possibility that these concepts may be considered as underlying mathematical structures in quantum gravity.